Uji Kadar Protein dan Lemak pada Sagu dengan Penambahan Ikan Cakalang Di Kabupaten Pulau Morotai - Titien Sofiati; Asy’ari Asy’ari; Jana Sidin (Jurnal Ilmiah Wahana Pendidikan, 2020)
Fish Sago is the result of diversification of fishing products that make use as traditional food of North Mollucas with the adding of Cakalang’s meat. This can help to increase the nutrition from sago palm by using a wood as the material tested. The purpose of this research is to know the level of proteins and fats on fish sago. The significance of this research is (1) to give the information to people about the processing of sago with Cakalang have a good enough nutrition values, (2) diversification and the developing of new fishing products have the economical values that important to the majority, right from public and private institutes that engaged with fish sago business. The examination of fish sago nutrition is at Environment Laboratory in Khairun University Ternate. The results showed that adds of Cakalang in sago can increase the protein level with 15,40%. However, the fats level in the fish sago more low with 1,31%.